Interplay between cell-surface receptor and intracellular NLR-mediated immune responses - Kourelis,J (New Phytologist, 2023)
The functional link between cell-surface receptors and intracellular NLR immune receptors is a critical aspect of plant immunity. To establish disease, successful pathogens have evolved mechanisms to suppress cell-surface immune signalling. In response, plants have adapted by evolving NLRs that recognize pathogen effectors involved in this suppression, thereby counteracting their immune-suppressing function. This ongoing co-evolutionary struggle has seemingly resulted in intertwined signalling pathways in some plant species, where NLRs form a separate signalling branch downstream of activated cell-surface receptor complexes essential for full immunity. Understanding these interconnected receptor networks could lead to novel strategies for developing durable disease resistance.